2003
DOI: 10.1242/jcs.00156
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the DNA replication competence of thexrs-5 mutant cells defective in Ku86

Abstract: The radiosensitive mutant xrs-5, a derivative of the Chinese hamster ovary (CHO) K1 cell line, is defective in DNA double-strand break repair and V(D)J recombination. The defective phenotypes of xrs-5 cells are complemented by the 86 kDa subunit of Ku antigen. OBA is a protein,previously purified from HeLa cells, that binds in a sequence-specific manner to mammalian origins of DNA replication. The DNA-binding subunit of OBA has been identified as Ku86. We tested the xrs-5 cell line for its ability to replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 95 publications
0
25
0
Order By: Relevance
“…Further support for a role of Ku in the initiation of DNA replication (Novac et al, 2001;Matheos et al, 2002;Matheos et al, 2003) is provided by the observed decrease in origin usage, reflected by a significant 3.4-4.5-fold decrease in nascent strand DNA abundance in Ku80 +/-cells (Fig. 7).…”
Section: Discussionmentioning
confidence: 75%
“…Further support for a role of Ku in the initiation of DNA replication (Novac et al, 2001;Matheos et al, 2002;Matheos et al, 2003) is provided by the observed decrease in origin usage, reflected by a significant 3.4-4.5-fold decrease in nascent strand DNA abundance in Ku80 +/-cells (Fig. 7).…”
Section: Discussionmentioning
confidence: 75%
“…The ability of the 20mer versions, found on human chromosome 19q13 and in the lamin B2 origin region, to confer autonomous replication activity when cloned into a plasmid was analyzed by the DpnI resistance assay, which is an indicator of semiconservative DNA replication, as previously described (36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…For transfections, HeLa cells were seeded in six-well plates at a density of 3 Â 10 4 per well, and f16 hours later were transfected with 3 Ag supercoiled plasmid DNA (2 Ag of each construct in Table 2 and 1 Ag pM1 SEAP), using FuGENE 6 transfection reagent (Roche Molecular Biochemicals) as per instructions of the manufacturer. At 72 hours post-transfection, low molecular weight DNA was isolated and digested with DpnI, the DpnI-digested and undigested DNA were used to transform the DH5a strain of Escherichia coli and the relative in vivo DNA replication of each transfected plasmid was determined by counting the number of colonies in a bacterial retransformation assay, as previously described (36)(37)(38). The levels of secreted human placental alkaline phosphatase, determined by the SEAP Reporter Gene Assay kit (Roche Molecular Biochemicals), as per specifications of the manufacturer, were used to normalize the transfection efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, Ku and Sir4 may be relying on some other silencer-recognition mechanism. In this regard, it is intriguing that the effects of yeast Ku on ORC binding in vitro have been reported (Shakibai et al 1996) and that in mammalian cells Ku associates with replication origins and has been found in a complex with known replication proteins, including ORC2 (Novac et al 2001;Matheos et al 2002Matheos et al , 2003. In addition, recent two-hybrid analyses of Orc subunits report an interaction between Orc2 and Sir4 (Matsuda et al 2007).…”
Section: Discussionmentioning
confidence: 99%